Method for producing sulfur-containing conductive composite, conductive polymer dispersion, conductive laminate and method for producing same
A sulfur-containing conductive composite with modified anion groups addresses the conductivity decline in π-conjugated polymers under harsh conditions, ensuring durable and stable conductive layers.
Patent Information
- Application Number
- JP2020157192
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-09-18
AI Technical Summary
Conductive layers formed from π-conjugated conductive polymers deteriorate in conductivity over time due to exposure to high temperature and high humidity environments.
A sulfur-containing conductive composite is developed, comprising a π-conjugated conductive polymer, a polyanion, and elemental sulfur, with anion groups modified by compounds like amine or quaternary ammonium compounds, to enhance durability and conductivity.
The conductive composite maintains excellent conductivity and durability under high temperature and high humidity conditions, with a conductive polymer dispersion exhibiting improved storage stability.
Smart Images

Figure 0007603401000001 
Figure 0007603401000002 
Figure 0007603401000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfur-containing conductive composite containing a π-conjugated conductive polymer and a method for producing the same, a conductive polymer dispersion, and a conductive laminate and a method for producing the same. [Background technology]
[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anionic group, and becomes dispersible in water. A conductive laminate having a conductive layer (conductive film) can be produced by applying a conductive polymer dispersion containing the conductive complex to a glass substrate, a film substrate, or the like. However, the conductive layer containing the conductive complex has a problem in that the conductivity decreases over time due to exposure to the atmosphere. As a method for alleviating this problem, a method of incorporating an antioxidant into the conductive layer has been disclosed (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5509462 Summary of the Invention [Problem to be solved by the invention]
[0004] However, there is a demand for a new conductive polymer dispersion to replace the invention disclosed in Patent Document 1. The present invention provides a sulfur-containing conductive composite capable of forming a conductive layer having excellent electrical conductivity and durability against exposure to a high-temperature and high-humidity environment, and a method for producing the same. The present invention also provides a conductive polymer dispersion containing the sulfur-containing conductive composite and having excellent storage stability. Furthermore, the present invention provides a conductive laminate having the conductive layer and a method for producing the same. [Means for solving the problem]
[0005] [1] A sulfur-containing conductive complex that contains a π-conjugated conductive polymer and a polyanion, and further contains elemental sulfur. [2] The sulfur-containing conductive composite according to [1], wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene) or the polyanion is polystyrenesulfonic acid. [3] The sulfur-containing conductive complex according to [1] or [2], wherein a portion of the anion groups of the polyanion is modified by reacting with an amine compound or a quaternary ammonium compound. [4] The sulfur-containing conductive composite according to [1] or [2], wherein a portion of the anion groups of the polyanion is modified by reaction with an epoxy compound. [5] A conductive polymer dispersion comprising a dispersion medium and the sulfur-containing conductive composite according to any one of [1] to [4]. [6] The conductive polymer dispersion according to [5], further comprising a binder component. [7] A conductive laminate comprising a substrate and a conductive layer formed on at least one surface of the substrate, the conductive layer comprising the sulfur-containing conductive composite according to any one of [1] to [4]. [8] A method for producing a conductive laminate, comprising applying the conductive polymer dispersion according to [5] or [6] to at least one surface of a substrate. [9] A method for producing a sulfur-containing conductive composite, the method comprising: mixing a solution containing elemental sulfur and an amine compound or a quaternary ammonium compound with a raw material liquid containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an aqueous dispersion medium, to obtain a reaction liquid; reacting the conductive complex with the amine compound or the quaternary ammonium compound, and further precipitating a sulfur-containing conductive composite containing elemental sulfur.
[10] A method for producing a sulfur-containing conductive composite, comprising: mixing a solution containing elemental sulfur and an epoxy compound with a raw material liquid containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an aqueous dispersion medium to obtain a reaction liquid; reacting the epoxy compound with the conductive complex, and further precipitating a sulfur-containing conductive composite containing elemental sulfur. Effect of the Invention
[0006] According to the sulfur-containing conductive composite of the present invention, a conductive layer having excellent durability and conductivity against exposure to a high-temperature and high-humidity environment can be formed. In addition, the conductive polymer dispersion of the present invention has excellent storage stability. The conductive laminate of the present invention has a conductive layer having excellent durability and conductivity against exposure to a high-temperature and high-humidity environment, and can be used, for example, as an electrode of a battery.
[0007] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production."
[0008] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <<Sulfur-containing conductive composite>> A first aspect of the present invention is a sulfur-containing conductive composite that contains a π-conjugated conductive polymer and a polyanion, and further contains elemental sulfur.
[0010] [π-conjugated conductive polymers] The π-conjugated conductive polymer may be any conductive organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0011] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable from the viewpoints of conductivity, transparency, and heat resistance. The sulfur-containing conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of π-conjugated conductive polymers.
[0012] [Polyanion] The polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for the π-conjugated conductive polymer, thereby improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The sulfur-containing conductive composite may contain one type of polyanion or two or more types of polyanions.
[0013] The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, and more preferably from 100,000 to 500,000. The mass average molecular weight is the average molecular weight based on mass measured by gel filtration chromatography and calculated in terms of pullulan.
[0014] A conductive complex is formed by doping a polyanion into a π-conjugated conductive polymer. However, in the polyanion, some anion groups are not doped into the π-conjugated conductive polymer, and there are excess anion groups that are not involved in the doping. Since these excess anion groups are hydrophilic groups, the conductive complex has high water dispersibility and low organic solvent dispersibility before reacting with an epoxy compound or the like, as described below. When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.
[0015] The content of the polyanion contained in the sulfur-containing conductive composite of this embodiment is preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, relative to 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or greater than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the amount of anion groups not involved in doping is appropriately suppressed, and the anion groups can be easily converted to hydrophobicity by reacting them with an epoxy compound, an amine compound, or a quaternary ammonium compound.
[0016] The polyanion contained in the sulfur-containing conductive composite of this embodiment may be modified by a reaction between excess anionic groups (hereinafter also referred to as "partial anionic groups") of the polyanion that are not involved in doping and at least one of an epoxy compound, an amine compound, and a quaternary ammonium compound. That is, the polyanion of the present invention may have one or more selected from the group consisting of a substituent (A) formed by a reaction between an epoxy compound and a partial anionic group, a substituent (B) formed by a reaction between an amine compound and a partial anionic group, and a substituent (C) formed by a reaction between a quaternary ammonium compound and a partial anionic group.
[0017] (Substituent A) The substituent (A) is presumed to be a group represented by the following formula (A1) or a group represented by the following formula (A2).
[0018] [ka]
[0019] [In formula (A1), R 1 , R 2 , R 3 , and R 4 are each independently a hydrogen atom or any substituent.
[0020] [ka]
[0021] [In formula (A2), m is an integer of 2 or more, 5 , multiple R 6 , multiple R 7 , and multiple R 8 are each independently a hydrogen atom or an arbitrary substituent, and multiple R 5 may be the same or different, and multiple R 6 may be the same or different, and multiple R 7 may be the same or different, and multiple R 8 may be the same or different.]
[0022] In formulae (A1) and (A2), the bond at the left end represents that the substituent (A) is substituted with a proton of an anionic group. Examples of the anionic group having a substituted proton include an anionic group having an active proton bonded to an oxygen atom, such as "-SO3H".
[0023] In formula (A1), R 1 , R 2 , R 3 , and R 4 Examples of the optional substituent of R include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. 1 and R 3 may be bonded to form a ring which may have a substituent. For example, R 1 and R 3 and R 1 and a divalent hydrocarbon group obtained by removing any one hydrogen atom from the monovalent hydrocarbon group of R 3 and a divalent hydrocarbon group obtained by removing any one hydrogen atom from the monovalent hydrocarbon group above, are bonded to each other at the carbon atoms from which the hydrogen atom has been removed to form a ring. In formula (A2), R5 , R 6 , R 7 , and R 8 Examples of the optional substituent of R include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. 5 and R 7 and may be bonded to form a ring which may have a substituent. Examples of the ring are the same as those mentioned above. In this specification, the term "optionally substituted" includes both cases where a hydrogen atom (-H) is replaced with a monovalent group and cases where a methylene group (-CH2-) is replaced with a divalent group. Examples of monovalent groups as substituents include alkyl groups having 1 to 4 carbon atoms, alkenyl groups having 2 to 4 carbon atoms, halogen atoms (such as fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms), and trialkoxysilyl groups (such as trimethoxysilyl groups). Examples of the divalent group as a substituent include an oxygen atom (-O-), -C(=O)-, and -C(=O)-O-. m is an integer of 2 or more, preferably 2 to 100, more preferably 2 to 50, and even more preferably 2 to 25. When m is equal to or more than the lower limit, the hydrophobicity of the conductive composite is sufficiently high. When m is equal to or less than the upper limit, it is possible to prevent the hydrophobicity from becoming too high or the conductivity from decreasing.
[0024] The epoxy compound is a compound having one or more epoxy groups in one molecule (an epoxy group-containing compound). From the viewpoint of preventing aggregation or gelation, the epoxy compound is preferably a compound having one epoxy group in one molecule. The epoxy compound that reacts with the conductive composite may be one type or two or more types.
[0025] Examples of monofunctional epoxy compounds having one epoxy group per molecule include ethylene oxide, propylene oxide, 2,3-butylene oxide, isobutylene oxide, 1,2-butylene oxide, 1,2-epoxyhexane, 1,2-epoxyheptane, 1,2-epoxypentane, 1,2-epoxyoctane, 1,2-epoxydecane, 1,3-butadiene monoxide, 1,2-epoxytetradecane, glycidyl methyl ether, 1,2-epoxyoctadecane, 1,2-epoxyhexadecane, and ethylene oxide. glycidyl ether, glycidyl isopropyl ether, tert-butyl glycidyl ether, 1,2-epoxyeicosane, 2-(chloromethyl)-1,2-epoxypropane, glycidol, epichlorohydrin, epibromohydrin, butyl glycidyl ether, 1,2-epoxyhexane, 1,2-epoxy-9-decane, 2-(chloromethyl)-1,2-epoxybutane, 2-ethylhexyl glycidyl ether, 1,2-epoxy-1H,1H,2H,2H,3H,3H-trifluorobutane, allyl glycidyl ether, tetracyanoethylene oxide, glycidyl butyrate, 1,2-epoxycyclooctane, glycidyl methacrylate, 1,2-epoxycyclododecane, 1-methyl-1,2-epoxycyclohexane, 1,2-epoxycyclopentadecane, 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 1,2-epoxy-1H,1H,2H,2H,3H,3H-heptadecafluorobutane, 3,4-epoxytetrahydrofuran, glycidyl stearate, 3-glycidyloxypropyl trimer Epoxysilane, epoxysuccinic acid, glycidyl phenyl ether, isophorone oxide, α-pinene oxide, 2,3-epoxynorbornene, benzyl glycidyl ether, diethoxy(3-glycidyloxypropyl)methylsilane, 3-[2-(perfluorohexyl)ethoxy]-1,2-epoxypropane, 1,1,1,3,5,5,5-heptamethyl-3-(3-glycidyloxypropyl)trisiloxane, 9,10-epoxy-1,5-cyclododecadiene, glycidyl 4-tert-butylbenzoate, 2,2-Bis(4-glycidyloxyphenyl)propane, 2-tert-butyl-2-[2-(4-chlorophenyl)]ethyloxirane, styrene oxide, glycidyl trityl ether, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-phenylpropylene oxide, cholesterol-5α,6α-epoxide, stilbene oxide, p-toluenesulfonic acid glycidyl, 3-methyl-3-phenylglycidic acid ethyl, N-propyl-N-(2,3-epoxypropyl)perfluoro-n- Examples of the glycidyl ethers include octyl sulfonamide, (2S,3S)-1,2-epoxy-3-(tert-butoxycarbonylamino)-4-phenylbutane, (R)-glycidyl 3-nitrobenzenesulfonate, glycidyl 3-nitrobenzenesulfonate, parthenolide, N-glycidylphthalimide, endrin, dieldrin, 4-glycidyloxycarbazole, 7,7-dimethyloctanoic acid [oxiranylmethyl], 1,2-epoxy-4-vinylcyclohexane, and higher alcohol glycidyl ethers having 10 to 16 carbon atoms.
[0026] The higher alcohol glycidyl ether is preferably at least one type of higher alcohol glycidyl ether having 10 to 16 carbon atoms, more preferably at least one type of higher alcohol glycidyl ether having 12 to 14 carbon atoms, and even more preferably at least one type of C12 (12 carbon atoms) higher alcohol glycidyl ether and C13 (13 carbon atoms) higher alcohol glycidyl ether.
[0027] Examples of polyfunctional epoxy compounds having two or more epoxy groups in one molecule include 1,6-hexanediol diglycidyl ether, 1,7-octadiene diepoxide, neopentyl glycol diglycidyl ether, 4-butanediol diglycidyl ether, 1,2:3,4-diepoxybutane, 1,2-cyclohexanedicarboxylate diglycidyl, triglycidyl isocyanurate, neopentyl glycol diglycidyl ether, 1,2:3,4-diepoxybutane, polyethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, and the like. Examples of the glycidyl ether include glycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerin diglycidyl ether, trimethylolpropane triglycidyl ether, trimethylolpropane polyglycidyl ether, hydrogenated bisphenol A diglycidyl ether, hexahydrophthalic acid diglycidyl ester, glycerin polyglycidyl ether, diglycerin polyglycidyl ether, polyglycerin polyglycidyl ether, sorbitol-based polyglycidyl ether, and ethylene oxide lauryl alcohol glycidyl ether.
[0028] Since the epoxy compound has high dispersibility in organic solvents, the molecular weight is preferably from 50 to 2,000. Furthermore, since the epoxy compound has high dispersibility in low-polarity hydrocarbon solvents and ester solvents, the epoxy compound preferably has a carbon number of from 4 to 120, more preferably from 7 to 100, even more preferably from 10 to 80, and particularly preferably from 15 to 50.
[0029] (Substituent B) The substituent (B) is presumed to be a group represented by the following formula (B).
[0030] -H.N. + R 11 R 12 R 13 (B) [In formula (B), R 11 ~R 13 are each independently a hydrogen atom or a hydrocarbon group which may have a substituent, provided that R 11 ~R 13 At least one of the groups is a hydrocarbon group which may have a substituent.]
[0031] In the substituent (B), the bond at the left end represents the bond between the negative charge of the anionic group and the positive charge of the amine compound. Examples of anionic groups that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0032] R in chemical formula (B) 11 ~R 13 is a hydrogen atom or a hydrocarbon group which may have a substituent. 11 ~R 13 is a substituent derived from an amine compound described later. Examples of the hydrocarbon group in the chemical formula (B) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0033] In order to enhance dispersibility in organic solvents, the amine compound preferably has a substituent having 4 or more carbon atoms on the nitrogen atom, more preferably has a substituent having 6 or more carbon atoms, and further preferably has a substituent having 8 or more carbon atoms on the nitrogen atom.
[0034] The amine compound is at least one selected from the group consisting of primary amines, secondary amines, and tertiary amines. The amine compound that reacts with the conductive composite may be one type or two or more types. Examples of primary amines include aniline, toluidine, benzylamine, and ethanolamine. Examples of secondary amines include diethanolamine, dimethylamine, diethylamine, dipropylamine, diphenylamine, dibenzylamine, and dinaphthylamine. Examples of tertiary amines include triethanolamine, trimethylamine, triethylamine, tripropylamine, tributylamine, trihexylamine, trioctylamine, triphenylamine, tribenzylamine, and trinaphthylamine. Among the amine compounds, tertiary amines are preferred, and at least one of trioctylamine and tributylamine is more preferred, since the conductive polymer dispersion of this embodiment can be easily produced.
[0035] (Substituent C) The substituent (C) is presumed to be a group represented by the following formula (C).
[0036] -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.
[0037] In the substituent (C), the bond at the left end represents the bond between the negative charge of the anion group and the positive charge of the quaternary ammonium cation. Examples of an anion group that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0038] R in chemical formula (C) 11 ~R14 R in chemical formula (C) is a hydrocarbon group which may have a substituent. 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in the chemical formula (C) include an aliphatic hydrocarbon group having 1 to 20 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0039] In order to enhance dispersibility in organic solvents, the quaternary ammonium compound preferably has a substituent on the nitrogen atom having 4 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 6 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 8 or more carbon atoms.
[0040] Specific examples of the quaternary ammonium compound include quaternary ammonium salts such as tetra-n-octylammonium salt, tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, tetranaphthylammonium salt, etc. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.
[0041] [Elemental sulfur] The elemental sulfur contained in the sulfur-containing conductive composite of this embodiment may be an elemental sulfur, and there is no limitation on the type of allotrope or crystal polymorphism. Although the detailed binding mode of elemental sulfur to the conductive complex has not been elucidated, it is speculated that charged sulfur molecules are in a state of being encapsulated in the conductive complex in a colloidal state.
[0042] The content of elemental sulfur in the sulfur-containing conductive composite of this embodiment is preferably 10 parts by mass or more and 1,000 parts by mass or less, more preferably 30 parts by mass or more and 500 parts by mass or less, still more preferably 50 parts by mass or more and 300 parts by mass or less, and particularly preferably 70 parts by mass or more and 150 parts by mass or less, relative to 100 parts by mass of the conductive composite consisting only of a π-conjugated conductive polymer and a polyanion. When it is at least the lower limit of the above range, the durability and electrical conductivity against exposure to a high-temperature and high-humidity environment are further improved, and the dispersibility in a dispersion medium is also further improved. When the content is equal to or less than the upper limit of the above range, the relative content of the conductive complex increases, and a decrease in conductivity that may occur due to an excessive content of elemental sulfur can be suppressed. The content of elemental sulfur contained in the sulfur-containing conductive composite of this embodiment can be quantified by a combustion method or an X-ray analysis method.
[0043] ≪Conductive polymer dispersion liquid≫ A second aspect of the present invention is a conductive polymer dispersion comprising a dispersion medium and the sulfur-containing conductive composite of the first aspect. In the conductive polymer dispersion of this embodiment, the sulfur-containing conductive composite may be in a dispersed state or a dissolved state. In this specification, unless otherwise specified, there is no distinction between dispersion and dissolution, and the term "dispersion" may be used simply.
[0044] The content of the sulfur-containing conductive complex relative to the total mass of the conductive polymer dispersion is, for example, preferably 0.1 mass % or more and 5 mass % or less, more preferably 0.2 mass % or more and 2 mass % or less, and even more preferably 0.3 mass % or more and 1 mass % or less. When the content is within the above range, the dispersibility of the sulfur-containing conductive composite is further improved, and the storage stability of the conductive polymer dispersion is further improved. Also, a uniform conductive layer having excellent conductivity can be formed.
[0045] <Dispersion medium> The dispersion medium contained in the conductive polymer dispersion of this embodiment is a liquid agent that disperses the sulfur-containing conductive composite. The dispersion medium contains at least one of water and an organic solvent. The polyanion of the sulfur-containing conductive composite may be modified to be hydrophobic as described above, or may not be hydrophobic. When the polyanion is hydrophobic, it is preferable to use an organic solvent as the dispersion medium. When the polyanion is not hydrophobic, it is preferable to use an aqueous dispersion medium as the dispersion medium.
[0046] (Organic solvent) The organic solvent may be a water-soluble organic solvent, a water-insoluble organic solvent, or a mixed solvent of a water-soluble organic solvent and a water-insoluble organic solvent. In this specification, a water-soluble organic solvent is an organic solvent that dissolves in an amount of 1 g or more in 100 g of water at 20°C, and a water-insoluble organic solvent is an organic solvent that dissolves in an amount of less than 1 g in 100 g of water at 20°C.
[0047] Examples of the water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, nitrogen atom-containing solvents, and ester-based solvents. Examples of alcohol-based solvents include methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 2-methyl-2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, allyl alcohol, ethylene glycol, propylene glycol, propylene glycol monomethyl ether, and ethylene glycol monomethyl ether. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dialkyl ether, and diethylene glycol diethyl ether. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the nitrogen atom-containing solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. The water-soluble organic solvent may be contained alone or in combination of two or more kinds. The water-soluble organic solvent is preferably an alcohol-based solvent or a ketone-based solvent, since this improves the coatability of the conductive polymer dispersion onto a glass substrate or a film substrate.
[0048] Examples of the non-water-soluble organic solvent include hydrocarbon solvents, etc. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include hexane, cyclohexane, pentane, heptane, octane, nonane, decane, and dodecane. Examples of aromatic hydrocarbon solvents include benzene, toluene, xylene, ethylbenzene, propylbenzene, and isopropylbenzene. The water-insoluble organic solvent may be contained alone or in combination of two or more kinds. Among the non-water-soluble organic solvents, aromatic hydrocarbon solvents are preferred, and toluene is more preferred, in terms of ease of production of the conductive polymer dispersion in this embodiment.
[0049] When the sulfur-containing conductive composite of this embodiment is hydrophobized by having any one of the above-mentioned substituents (A), (B), and (C), the content of the organic solvent relative to the total mass of the dispersion medium is preferably more than 50 mass%, more preferably 70 mass% or more and 100 mass% or less, and even more preferably 90 mass% or more and 99.9 mass% or less. When the content ratio of the organic solvent is within the above range, the hydrophobized sulfur-containing conductive composite can be easily dispersed, and the conductive layer can be easily formed.
[0050] (High boiling point solvent) The dispersion medium may further contain a high-boiling point solvent having a boiling point at 1 atmosphere (101,325 Pascals) in the range of 150° C. to 250° C. By containing a high-boiling point solvent, effects such as improved electrical conductivity can be obtained. When the dispersion medium contains a high boiling point solvent, it also contains a dispersion medium other than a high boiling point solvent (a dispersion medium having a boiling point of less than 150° C. at 1 atmospheric pressure). The dispersion medium may contain one type of high-boiling point solvent or two or more types of high-boiling point solvents. When the dispersion medium contains a high-boiling point solvent, the dispersion medium other than the high-boiling point solvent may contain one type of high-boiling point solvent or two or more types of high-boiling point solvents.
[0051] Examples of high boiling point solvents include water-soluble organic solvents and water-insoluble organic solvents, the definitions of which are the same as those described above.
[0052] Examples of the high-boiling water-soluble organic solvent include alcohol-based solvents, ether-based solvents, ketone-based solvents, nitrogen atom-containing solvents, and sulfur atom-containing solvents. Examples of alcohol-based solvents include polyhydric alcohols such as ethylene glycol (boiling point 198°C), 1,2-propanediol (also known as propylene glycol, boiling point 188°C), 1,3-propanediol (boiling point 214°C), 1,2-butanediol (boiling point 194°C), 1,3-butanediol (boiling point 207°C), 1,4-butanediol (boiling point 228°C), dipropylene glycol (boiling point 232°C, mixture of isomers), and diethylene glycol (boiling point 245°C). Examples of ether solvents include diethylene glycol dimethyl ether (boiling point 162° C.) and diethylene glycol diethyl ether (boiling point 188° C.). Examples of ketone solvents include methyl amyl ketone (boiling point 151° C.) and diacetone alcohol (boiling point 168° C.). Examples of nitrogen atom-containing solvents include N-methylpyrrolidone (boiling point 202° C.), N-methylacetamide (boiling point 206° C.), dimethylacetamide (boiling point 165° C.), and N,N-dimethylformamide (boiling point 153° C.). An example of the sulfur atom-containing solvent is dimethyl sulfoxide (boiling point: 189° C.).
[0053] Examples of the high-boiling point water-insoluble organic solvent include hydrocarbon solvents, etc. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include nonane (boiling point 151° C.), decane (boiling point 174° C.), and dodecane (boiling point 216° C.). Examples of aromatic hydrocarbon solvents include propylbenzene (boiling point 159° C.) and isopropylbenzene (boiling point 152° C.).
[0054] Among the above examples, alcohol-based high boiling point solvents are preferred because they provide a greater effect of improving electrical conductivity. Among the alcohol-based high-boiling point solvents, ethylene glycol (boiling point 198°C), 1,2-propanediol (boiling point 188°C), 1,3-propanediol (boiling point 214°C), and dimethyl sulfoxide (boiling point 189°C) are preferred because of their excellent effects in improving electrical conductivity, and ethylene glycol, 1,2-propanediol, and 1,3-propanediol are more preferred.
[0055] The content ratio of the high boiling point solvent relative to 100 parts by mass of the sulfur-containing conductive composite contained in the conductive polymer dispersion of this embodiment is preferably 300 parts by mass to 10,000 parts by mass, more preferably 500 parts by mass to 5,000 parts by mass, and even more preferably 800 parts by mass to 3,000 parts by mass. When in the above range, the conductivity of the formed conductive layer is further improved.
[0056] The content of the high-boiling point solvent relative to the total mass of the conductive polymer dispersion of this embodiment is preferably from 1% by mass to 10% by mass, more preferably from 2% by mass to 8% by mass, and even more preferably from 3% by mass to 6% by mass. When in the above range, the conductivity of the formed conductive layer is further improved.
[0057] The ratio of the high boiling point solvent and the dispersion medium other than the high boiling point solvent contained in the conductive polymer dispersion liquid of this embodiment is preferably such that the total mass of the high boiling point solvent (M1) is less than the total mass of the dispersion medium other than the high boiling point solvent (M2). The M2 / M1 ratio is preferably 5 to 35, more preferably 10 to 30, and even more preferably 15 to 25. When the content is within the above range, the conductivity of the conductive layer formed can be further increased.
[0058] (aqueous dispersion medium) The aqueous dispersion medium is water or a mixture of water and a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvents may be used alone or in combination of two or more. The content of water relative to the total mass of the aqueous dispersion medium is 50% by mass or more, preferably 60% by mass or more, more preferably 80% by mass or more, and may be 100% by mass.
[0059] <Binder components> The conductive polymer dispersion of this embodiment may contain a binder component. The binder component is a resin other than the π-conjugated conductive polymer and the polyanion or a precursor thereof, and is a thermoplastic resin, or a curable monomer or oligomer that is cured when the conductive layer is formed. The thermoplastic resin becomes the binder resin as it is, and the curable monomer or oligomer becomes the resin formed by curing becomes the binder resin. The binder component may be used alone or in combination of two or more kinds.
[0060] Specific examples of binder resins derived from binder components include polyvinyl alcohol resins, acrylic resins (acrylic compounds), polyester resins, polyurethane resins, polyimide resins, polyether resins, melamine resins, and silicones.
[0061] The curable monomer or oligomer may be a thermosetting monomer or oligomer, or a photocurable monomer or oligomer. Here, the oligomer refers to a polymer having a mass average molecular weight of less than 10,000. Examples of the curable monomer include an acrylic monomer (acrylic compound), an epoxy monomer, an organosiloxane, etc. Examples of the curable oligomer include an acrylic oligomer (acrylic compound), an epoxy oligomer, a silicone oligomer (curable silicone), etc. When an acrylic monomer or an acrylic oligomer is used as the binder component, it can be easily cured by heating or light irradiation. When an organosiloxane or a silicone oligomer is used as the binder component, it is possible to impart releasability (non-adhesiveness) to the conductive layer.
[0062] When the composition contains a curable monomer or oligomer, it is preferable to further contain a curing catalyst. For example, when the composition contains a thermosetting monomer or oligomer, it is preferable to contain a thermal polymerization initiator that generates radicals by heating, and when the composition contains a photocurable monomer or oligomer, it is preferable to contain a photopolymerization initiator that generates radicals by light irradiation. In addition, when the composition contains an organosiloxane or silicone oligomer, it is preferable to contain a platinum catalyst for curing.
[0063] When the dispersion medium of the conductive polymer dispersion is an aqueous dispersion medium, the binder resin contained therein is preferably a water-dispersible resin, more preferably a water-dispersible emulsion resin. The water-dispersible resin is an emulsion resin or a water-soluble resin.
[0064] The content ratio of the binder component in the conductive polymer dispersion is preferably 10 parts by mass or more and 10,000 parts by mass or less, more preferably 50 parts by mass or more and 5,000 parts by mass or less, and even more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the sulfur-containing conductive composite. When the content is equal to or greater than the lower limit of the above range, the film formability and film strength when the conductive polymer dispersion is applied to a glass substrate or a film substrate can be improved, and the durability of the conductive layer can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to a decrease in the content ratio of the sulfur-containing conductive composite can be suppressed.
[0065] (Antioxidants) The conductive polymer dispersion of this embodiment may contain an antioxidant (stabilizer). Among the antioxidants, phenol-based antioxidants are preferred. Among the phenol-based antioxidants, at least one of gallic acid and esters of gallic acid is preferred. Gallic acid and esters of gallic acid have high antioxidant properties and also have the effect of improving electrical conductivity. Examples of esters of gallic acid include methyl gallate, ethyl gallate, and propyl gallate.
[0066] The content of the antioxidant is preferably 5 parts by mass or more and 1000 parts by mass or less, more preferably 10 parts by mass or more and 500 parts by mass or less, and even more preferably 20 parts by mass or more and 100 parts by mass or less, per 100 parts by mass of the sulfur-containing conductive composite. When the content is equal to or greater than the lower limit of the above range, the oxidation of the sulfur-containing conductive composite can be further prevented. When the content is equal to or less than the upper limit of the above range, a decrease in the electrical conductivity of the sulfur-containing conductive composite can be prevented.
[0067] (Other additives) The conductive polymer dispersion may contain other additives. The additives are not particularly limited as long as the effects of the present invention can be obtained. For example, surfactants, inorganic conductive agents, antifoaming agents, coupling agents, antioxidants, ultraviolet absorbing agents, etc. can be used. However, the additive is one other than the above-mentioned π-conjugated conductive polymer, polyanion, elemental sulfur, water-soluble organic solvent, high boiling point solvent, and phenol-based antioxidant. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having an epoxy group, a vinyl group or an amino group. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers.
[0068] When the conductive polymer dispersion contains the additive, the content ratio thereof is appropriately determined depending on the type of additive, and can be, for example, in the range of 0.001 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the sulfur-containing conductive composite.
[0069] <Method for producing sulfur-containing conductive composite> [Precipitation process] A third aspect of the present invention is a method for producing a sulfur-containing conductive composite, the method comprising: mixing a solution containing elemental sulfur and a compound (Z) with a raw material liquid containing a conductive composite containing a π-conjugated conductive polymer and a polyanion, and an aqueous dispersion medium to obtain a reaction liquid; reacting the conductive composite with the compound (Z), and precipitating a sulfur-containing conductive composite containing elemental sulfur. Here, the compound (Z) is at least one selected from the epoxy compound, amine compound, and quaternary ammonium compound described above. The explanation of these compounds is the same as that in the first embodiment, so the overlapping explanation will be omitted.
[0070] The raw material liquid is a dispersion liquid in which a conductive complex containing a π-conjugated conductive polymer and a polyanion is contained in an aqueous dispersion medium. Here, the aqueous dispersion medium is water or a mixture of water and a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The aqueous dispersion medium may contain one type of water-soluble organic solvent or two or more types of water-soluble organic solvents. The content of water relative to the total mass of the aqueous dispersion medium is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass.
[0071] The raw material liquid can be obtained, for example, by chemically oxidizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion. A commercially available conductive polymer dispersion may be used as the raw material liquid. In the chemical oxidation polymerization, known catalysts and oxidizing agents can be used. Examples of catalysts include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of oxidizing agents include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate. The oxidizing agent can return the reduced catalyst to its original oxidized state.
[0072] The conductive complex contained in the raw material liquid may be in a dispersed state or a dissolved state. In this specification, unless otherwise specified, no distinction is made between the dispersed state and the dissolved state.
[0073] The content of the conductive complex relative to the total mass of the raw material liquid is, for example, preferably 0.1 mass % to 5 mass %, more preferably 0.3 mass % to 3 mass %, and even more preferably 0.5 mass % to 1.5 mass %. When the amount is within the above range, the dispersibility of the conductive composite in the raw material liquid is increased, and the reaction carried out in the subsequent step becomes favorable.
[0074] From the viewpoint of increasing the solubility of the elemental sulfur to be mixed with the raw material liquid, it is preferable to mix the elemental sulfur in the form of a sulfur solution in which the elemental sulfur is dissolved in a separate solvent in advance, rather than mixing the elemental sulfur in the solid state. Carbon disulfide is a preferable solvent for dissolving elemental sulfur. The content of elemental sulfur relative to the total mass of the sulfur solution is, for example, about 1% by mass or more and 10% by mass or less.
[0075] The content of elemental sulfur relative to the total mass of the reaction liquid is, for example, about 0.1% by mass or more and 1% by mass or less.
[0076] When the compound (Z) to be mixed with the raw material liquid has low solubility in water, it is preferable to mix a water-soluble organic solvent with the raw material liquid in order to increase the solubility of the compound (Z) in the reaction liquid. Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The water-soluble organic solvents may be used alone or in combination of two or more.
[0077] The content of the water-soluble organic solvent relative to the total mass of the reaction liquid is preferably 50% by mass or more and 85% by mass or less, more preferably 60% by mass or more and 80% by mass or less, and even more preferably 65% by mass or more and 75% by mass or less. When the content is equal to or more than the lower limit of the above range, the solubility of the compound (Z) and the sulfur solution can be increased. When it is equal to or less than the upper limit of the above range, the dispersibility of the conductive composite can be improved.
[0078] In the reaction solution obtained by mixing the epoxy compound with the raw material solution, the epoxy group of the epoxy compound reacts with a part of the anion group of the polyanion. As a result, a substituent (A) is formed and the conductive complex becomes hydrophobic, making it difficult to stably disperse in a dispersion medium containing water, and the conductive complex precipitates to become a precipitate. When the conductive complex precipitates, it contains elemental sulfur to become a sulfur-containing conductive complex. The reaction solution may be heated to promote the reaction of the epoxy compound, and the heating temperature is preferably 40° C. or higher and 100° C. or lower. The amount of the epoxy compound added is preferably 10 parts by mass or more and 10,000 parts by mass or less, more preferably 100 parts by mass or more and 5,000 parts by mass or less, and even more preferably 500 parts by mass or more and 3,000 parts by mass or less, relative to 100 parts by mass of the conductive composite. When the content is equal to or more than the lower limit of the above range, the hydrophobicity of the sulfur-containing conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted epoxy compound can be prevented.
[0079] In the reaction solution obtained by mixing the raw material liquid with an amine compound, the amine compound reacts with a part of the anion group of the polyanion. As a result, a substituent (B) is formed and the conductive complex becomes hydrophobic, making it difficult to stably disperse in a dispersion containing water, and the conductive complex precipitates to become a precipitate. During the precipitation, the conductive complex contains elemental sulfur to become a sulfur-containing conductive complex. The amount of the amine compound added is preferably 1 part by mass to 10,000 parts by mass, more preferably 10 parts by mass to 5,000 parts by mass, and even more preferably 50 parts by mass to 1,000 parts by mass, per 100 parts by mass of the conductive composite. When the content is equal to or more than the lower limit of the above range, the hydrophobicity of the sulfur-containing conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted amine compound can be prevented.
[0080] In the reaction solution obtained by mixing the raw material solution with a quaternary ammonium compound, the quaternary ammonium compound reacts with some of the anion groups of the polyanion. This forms a substituent (C) and the conductive complex becomes hydrophobic, making it difficult to stably disperse in a dispersion containing water, and the conductive complex precipitates to form a precipitate. During the precipitation, the conductive complex contains elemental sulfur to form a sulfur-containing conductive complex. The amount of the quaternary ammonium compound added is preferably 1 part by mass or more and 10,000 parts by mass or less, more preferably 10 parts by mass or more and 5,000 parts by mass or less, and even more preferably 50 parts by mass or more and 1,000 parts by mass or less, per 100 parts by mass of the conductive composite. When the content is equal to or more than the lower limit of the above range, the hydrophobicity of the sulfur-containing conductive composite is sufficiently high, and the dispersibility in organic solvents is improved. When the content is equal to or less than the upper limit of the above range, a decrease in electrical conductivity due to unreacted quaternary ammonium compound can be prevented.
[0081] [Preparative separation process] The precipitate of the sulfur-containing conductive composite precipitated in the reaction liquid can be separated by various methods, such as a method of allowing the precipitate to settle naturally at the bottom of a container containing the reaction liquid and removing the supernatant, a method of sucking and recovering the precipitate floating in the upper layer of the reaction liquid, a method of filtering the reaction liquid to obtain a precipitate on a filter, a method of forming pellets of the precipitate at the bottom of a container containing the reaction liquid by centrifugation, and a method of spraying the reaction liquid into a gas and drying it to obtain a dried precipitate.
[0082] The precipitate separated from the reaction solution is preferably washed with water or an organic solvent since the reaction solution containing the catalyst, oxidizing agent, etc. is attached to the precipitate. Specifically, for example, the precipitate is added to a washing solution made of water or an organic solvent, stirred, and then precipitated again, thereby recovering the precipitate from the washing solution.
[0083] [Organic solvent addition process] An organic solvent is added to the separated sulfur-containing conductive complex (precipitate) and the mixture is stirred to obtain a conductive polymer dispersion. The organic solvent may be any of the organic solvents contained in the conductive polymer dispersion of the second embodiment. Among them, one or more selected from alcohol-based solvents, ketone-based solvents, and ester-based solvents are preferred, and one or more selected from isopropanol, methyl ethyl tonne, and ethanol are more preferred. By using these suitable organic solvents, the dispersibility of the sulfur-containing conductive composite in the conductive polymer dispersion can be further improved.
[0084] It is preferable to add an organic solvent to the sulfur-containing conductive composite and then stir the mixture to disperse it. The stirring method is not particularly limited, and the mixture may be stirred with a weak shear force such as a stirrer, or may be stirred with a dispersing machine with a high shear force (such as a homogenizer).
[0085] The content of the sulfur-containing conductive complex relative to the total mass of the conductive polymer dispersion obtained by adding an organic solvent to the sulfur-containing conductive complex is, for example, preferably 0.1 mass % or more and 5 mass % or less, more preferably 0.2 mass % or more and 2 mass % or less, and even more preferably 0.3 mass % or more and 1 mass % or less. When the content is within the above range, the dispersibility of the sulfur-containing conductive composite is further improved, and the storage stability of the conductive polymer dispersion is further improved.
[0086] The conductive polymer dispersion may further contain the above-mentioned high boiling point solvent, binder component, and other additives. The conductive polymer dispersion to which these additives have been added is sometimes called a paint.
[0087] The content of the sulfur-containing conductive complex relative to the total mass of the coating material is, for example, preferably 0.1 mass % or more and 5 mass % or less, more preferably 0.2 mass % or more and 2 mass % or less, and even more preferably 0.3 mass % or more and 1 mass % or less. When the content is within the above range, the dispersibility of the sulfur-containing conductive composite is further improved, and a uniform conductive layer having excellent conductivity can be formed.
[0088] <Conductive laminate> A fourth aspect of the present invention is a conductive laminate comprising a substrate and a conductive layer formed on at least one surface of the substrate, the conductive layer including the sulfur-containing conductive composite of the first aspect.
[0089] [Conductive layer] The average thickness of the conductive layer provided on at least one surface of the substrate is, for example, preferably 10 nm to 100 μm, more preferably 20 nm to 50 μm, and even more preferably 30 nm to 30 μm. When the average thickness of the conductive layer is equal to or greater than the lower limit, a sufficiently high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0090] The surface resistance value, which indicates a measure of good conductivity of the conductive layer of this embodiment, is, for example, 100 to 5000 Ω / sq., preferably 100 to 3000 Ω / sq., and more preferably 100 to 2000 Ω / sq.
[0091] [Base material] The substrate constituting the conductive laminate of this embodiment may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0092] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably the same type of resin as the binder resin, and among these, a polyester resin such as polyethylene terephthalate is preferred.
[0093] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesiveness of the conductive layer formed from the conductive polymer dispersion.
[0094] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0095] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0096] The average thickness of the glass substrate is preferably 100 μm or more and 3000 μm or less, and more preferably 100 μm or more and 1000 μm or less. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to be broken, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to making the conductive laminate thinner. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0097] <Method for manufacturing conductive laminate> A fifth aspect of the present invention is a method for producing a conductive laminate, comprising applying the conductive polymer dispersion of the second aspect to at least one surface of a substrate. The conductive laminate of the fourth aspect can be produced by the production method of this aspect.
[0098] Examples of a method for applying (coating) the conductive polymer dispersion of the second embodiment to an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0099] The amount of conductive polymer dispersion applied to the film substrate is not particularly limited, but taking into consideration uniform and even application, conductivity, and film strength, a solid content of 0.01 g / m 2 More than 10.0g / m2 The following ranges are preferred:
[0100] The coating film made of the conductive polymer dispersion applied onto the substrate is dried to remove the dispersion medium, thereby obtaining a conductive laminate in which a conductive layer (conductive film) is formed by hardening the coating film. Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 150° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 1 minute to 30 minutes, more preferably 5 minutes to 15 minutes.
[0101] ≪Electrode≫ A sixth aspect of the present invention is an electrode comprising a conductive layer comprising the sulfur-containing conductive composite of the first aspect. The shape of the electrode is not particularly limited, and examples thereof include known electrode shapes such as a plate, sheet, film, rod, column, and the like. The average thickness of the plate-, sheet- or film-like electrodes is, for example, preferably 0.01 μm or more and 1000 μm or less, and more preferably 0.1 μm or more and 100 μm or less, from the viewpoint of achieving both a reduction in electrical resistance and a thin electrode. The average thickness of a plate-, sheet-, or film-like electrode is the average value of the thickness measurements taken at 10 or more randomly selected points on the cross section of the electrode observed using a magnifying observation means such as a measuring microscope. The electrode of this embodiment may be supported by a substrate, or may be an independent electrode. When the electrode of this embodiment is used as an electrode for a lithium ion secondary battery, it may be either a positive electrode or a negative electrode.
[0102] The conductive layer constituting the electrode may contain one or more carbon materials. Examples of carbon materials include carbon black, graphite, vapor-grown carbon fibers, carbon nanofibers, carbon nanotubes, and graphene. The content of the carbon material relative to the total mass of the conductive layer can be, for example, from 0 mass % to 10 mass %.
[0103] The conductive layer constituting the electrode may contain one or more types of metal particles. Examples of metal particles include silver particles, copper particles, gold particles, and aluminum particles. The content of the metal particles relative to the total mass of the conductive layer can be, for example, from 0 mass % to 10 mass %.
[0104] <Electrode manufacturing method> Examples of the method for producing the electrode of this embodiment include a method in which the conductive polymer dispersion of the second embodiment is applied to a desired substrate, and dried to form an electrode layer (conductive layer) containing the sulfur-containing conductive composite of the first embodiment on the surface of the substrate. The conductive polymer dispersion can further contain the carbon material and the metal particles. As the substrate to which the conductive polymer dispersion is applied, a substrate supporting an electrode active material layer of a known battery can be applied, and examples thereof include metal materials such as metal foils and metal plates. Examples thereof include copper foils, aluminum foils, and stainless steel plates. Also, known resin films or resin plates may be used as the substrate. The coating method is not particularly limited, and a conventional method may be applied.
[0105] <Battery> It is also possible to manufacture a battery or a capacitor equipped with the electrode of this embodiment. The battery may be a primary battery or a secondary battery. The form of the battery is not particularly limited, and examples of the battery include known battery forms such as a dry battery, an electrode-stacked laminate battery, and a button battery. The battery generally has a positive electrode, a negative electrode, and an electrolyte. The electrode in this embodiment may be a positive electrode or a negative electrode. The positive electrode and the negative electrode in the battery are preferably insulated from each other by a separator such as a nonwoven fabric. EXAMPLES
[0106] (Production Example 1) 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium polystyrene sulfonate-containing solution to obtain a polystyrene sulfonic acid-containing solution. Then, about 1000ml of the polystyrene sulfonic acid-containing solution was removed by ultrafiltration, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solution was removed by ultrafiltration. The above ultrafiltration operation was repeated three times. Furthermore, about 2000ml of ion-exchanged water was added to the obtained filtrate, and about 2000ml of the solution was removed by ultrafiltration. This ultrafiltration operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.
[0107] (Production Example 2) 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to carry out the reaction. 2000 ml of ion-exchanged water was added to the reaction solution, and about 2000 ml of the solution was removed by ultrafiltration. This procedure was repeated three times. Then, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, about 2000 ml of the solution was removed by ultrafiltration, 2000 ml of ion-exchanged water was added to this, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Furthermore, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated five times to obtain a 1.2 mass% aqueous dispersion of polystyrenesulfonic acid-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS aqueous dispersion).
[0108] Example 1 A sulfur solution was prepared by dissolving 1.0 g of elemental sulfur (colloidal, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 20 g of carbon disulfide. This sulfur solution was mixed with 100 g (solid content 1.2 g) of the PEDOT-PSS aqueous dispersion of Production Example 2, 215 g of isopropanol, and 5.0 g of trioctylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) to obtain a reaction solution, which was stirred at 24°C for 1 hour to precipitate a sulfur-containing conductive complex. The precipitate of this sulfur-containing conductive complex contains elemental sulfur and has a structure in which trioctylamine reacts with a part of the sulfonic acid group of PSS. This precipitate was isolated by filtration and washed three times with 100 g of methanol to obtain 2.4 g of a deep blue sulfur-containing conductive complex.
[0109] Example 2 A sulfur solution was prepared by dissolving 1.0 g of elemental sulfur (manufactured by Fuji Film Wako Pure Chemical Industries, sulfur flower) in 20 g of carbon disulfide. This sulfur solution was mixed with 100 g (solid content 1.2 g) of the PEDOT-PSS aqueous dispersion of Production Example 2, 275 g of methanol, and 15.0 g of glycidyl lauryl ether (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) to obtain a reaction solution, which was stirred at 42°C for 4 hours to precipitate a sulfur-containing conductive complex. The precipitate of this sulfur-containing conductive complex contains elemental sulfur and has a structure in which a part of the sulfonic acid group of PSS has reacted with an epoxy compound. The precipitate was isolated by filtration and washed three times with 100 g of methanol to obtain 2.1 g of a deep blue sulfur-containing conductive complex.
[0110] Example 3 A sulfur solution was prepared by dissolving 1.0 g of elemental sulfur (manufactured by Fuji Film Wako Pure Chemical Industries, sulfur flower) in 20 g of carbon disulfide. This sulfur solution was mixed with 100 g (solid content 1.2 g) of the PEDOT-PSS aqueous dispersion of Production Example 2, 200 g of ethanol, and 2.5 g of tetraoctylammonium bromide (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) to obtain a reaction solution, which was stirred at 24°C for 1 hour to precipitate a sulfur-containing conductive complex. The precipitate of this sulfur-containing conductive complex contains elemental sulfur and has a structure in which tetraoctylammonium salt reacts with a part of the sulfonic acid group of PSS. This precipitate was isolated by filtration and washed three times with 100 g of methanol to obtain 2.3 g of a deep blue sulfur-containing conductive complex.
[0111] Example 4 200 g of isopropanol was added to 1.0 g of the sulfur-containing conductive composite obtained in Example 1, and the mixture was dispersed using a high-pressure homogenizer to obtain an isopropanol dispersion of the sulfur-containing conductive composite. 100 g of this isopropanol dispersion was added to 5 g of ethylene glycol, 0.1 g of gallic acid monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., stabilizer), and 0.5 g of Mobital B30H (manufactured by Kuraray Co., Ltd., butyral resin) as a binder component, and the mixture was stirred to obtain a coating material. The resulting coating material was then applied to alkali-free glass (Corning Eagle XG 75 mm x 75 mm x 0.7 mm) using a spin coater (Mikasa MS-B100, 700 rpm) to form a coating film. The coating film was dried by heating at 100°C for 10 minutes to obtain glass with a conductive film.
[0112] Example 5 200g of methyl ethyl ketone was added to 1.0g of the sulfur-containing conductive composite obtained in Example 2, and dispersed with a high-pressure homogenizer to obtain a methyl ethyl ketone dispersion of the sulfur-containing conductive composite. 100g of this methyl ethyl ketone dispersion, 5g of ethylene glycol, 0.1g of gallic acid monohydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., stabilizer), and 0.5g of Mobital B30H (manufactured by Kuraray Co., Ltd., butyral resin) as a binder component were added and mixed by stirring to obtain a paint. Using this paint, glass with a conductive film was produced in the same manner as in Example 4.
[0113] Example 6 An isopropanol dispersion was obtained and a coating material was prepared in the same manner as in Example 4, except that the sulfur-containing conductive composite obtained in Example 3 was used. A glass with a conductive film was prepared in the same manner as in Example 4 using this coating material.
[0114] Comparative Example 1 A precipitate of the reaction product was obtained in the same manner as in Example 1 except that no sulfur solution was used, and then an isopropanol dispersion, a paint, and glass with a conductive film were prepared in the same manner as in Example 4.
[0115] Comparative Example 2 A precipitate of the reaction product was obtained in the same manner as in Example 2, except that no sulfur solution was used. Then, a methyl ethyl ketone dispersion, a paint, and glass with a conductive film were prepared in the same manner as in Example 5.
[0116] Comparative Example 3 A precipitate of the reaction product was obtained in the same manner as in Example 3 except that no sulfur solution was used, and then an isopropanol dispersion, a paint, and glass with a conductive film were prepared in the same manner as in Example 4.
[0117] <Evaluation> For the glass with conductive film produced in each example, the results of the following evaluation items are shown in Table 1.
[0118] [Surface resistance measurement] The surface resistance value of the conductive film (conductive layer) was measured using a resistivity meter (Loresta manufactured by Nitto Seiko Analytech Co., Ltd.) under the condition of an applied voltage of 10V.
[0119] [Durability evaluation] The surface resistance of each example of glass with conductive film was measured within 1 hour after preparation (initial surface resistance), and the surface resistance after leaving the conductive layer exposed to high temperature and high humidity conditions (temperature 85°C and humidity 85%) for 200 hours (surface resistance after exposure to high temperature and high humidity) was measured. The rate of change in surface resistance (surface resistance after exposure / initial surface resistance) was used as an index of durability. The closer the rate of change in surface resistance is to 1, the higher the durability.
[0120] [Evaluation of dispersion stability] The isopropanol dispersion or methyl ethyl ketone dispersion of each example was stored at 40° C. for one month, and the presence or absence of solid precipitation was visually evaluated.
[0121] [Table 1]
[0122] The paints of Examples 4 to 6 contain a sulfur-containing conductive complex, and therefore the conductive layers formed using these had lower initial surface resistance values, lower surface resistance values after exposure to a high-temperature, high-humidity environment, and smaller rates of change before and after exposure, compared to Comparative Examples 1 to 3. Furthermore, the conductive polymer dispersions containing the sulfur-containing conductive complexes used to prepare the paints of Examples 4 to 6 had excellent storage stability and were less likely to generate solid matter.
Claims
1. A conductive polymer dispersion in which a sulfur-containing conductive complex containing a π-conjugated conductive polymer, a polyanion, and elemental sulfur is dispersed in a colloidal state in a dispersion medium, A part of the anion groups of the polyanion is modified by reacting with an amine compound or a quaternary ammonium compound. Conductive polymer dispersion.
2. A conductive polymer dispersion in which a sulfur-containing conductive complex containing a π-conjugated conductive polymer, a polyanion, and elemental sulfur is dispersed in a colloidal state in a dispersion medium, A conductive polymer dispersion, in which a part of anion groups of the polyanion is modified by reaction with an epoxy compound.
3. 3. The conductive polymer dispersion according to claim 1, wherein the π-conjugated conductive polymer is poly(3,4-ethylenedioxythiophene), or the polyanion is polystyrenesulfonic acid.
4. The conductive polymer dispersion according to claim 1 , further comprising a binder component.
5. A conductive laminate comprising: a substrate; and a conductive layer formed on at least one surface of the substrate, the conductive layer being made of a cured product of the conductive polymer dispersion according to any one of claims 1 to 4.
6. A method for producing a conductive laminate, comprising applying the conductive polymer dispersion according to any one of claims 1 to 4 to at least one surface of a substrate.
7. A method for producing a sulfur-containing conductive complex, comprising: mixing a solution containing elemental sulfur and an amine compound or a quaternary ammonium compound with a raw material liquid containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an aqueous dispersion medium, to obtain a reaction liquid; reacting the conductive complex with the amine compound or the quaternary ammonium compound, and further precipitating a sulfur-containing conductive complex containing the elemental sulfur.
8. A method for producing a sulfur-containing conductive composite, comprising: mixing a solution containing elemental sulfur and an epoxy compound with a raw material liquid containing a conductive complex containing a π-conjugated conductive polymer and a polyanion, and an aqueous dispersion medium, to obtain a reaction liquid; reacting the epoxy compound with the conductive complex, and further precipitating a sulfur-containing conductive composite containing the elemental sulfur.
Citation Information
Patent Citations
Production method of semiconductor pellet
JP1980009462A
Electroconductive solid matter, method for producing the same, and electroconductive polymer solution
JP2008045061A
Composite consisting of sulfur and conductive polymer
JP2011222389A
Positive electrode mixture and all-solid-state lithium sulfur battery
JP2015176849A
Conductive polymer dispersion, method of manufacturing the same, and method of manufacturing conductive film
JP2018203858A
